상안와벽 및 상안와연 골절의 치험례 - 이재열(Jae-Yeol Lee); 이성탁(Sung-Tak Lee); 김용덕(Yong-Deok Kim); 신상훈(Sang-Hun Shin),김욱규(Uk-Kyu Kim); 정인교(In-Kyo Chung); 황대석(Dae-Seok Hwang) (Journal of the Korean Association of Oral and Maxillofacial Surgeons, 2011)
Orbital roof and supraorbital ridge fractures are frequently associated with high energy concomitant craniofacial trauma. When a displacement of the orbital roof and supraorbital rim occurs, exploration, stabilization and reconstruction are warranted to limit the ocular complications. The management of fractures involving the frontal sinus must consider the possible need for obliteration or cranialization of the sinus. Many incisions have been described and used to approach these fractures, such as a coronal incision, eyebrow incision, and an incision through the laceration. We report 3 cases of orbital roof and supraorbital ridge fracture patients with a review of the relevant literature. KCI Citation Count: 0